MEDIASI KEMAMPUAN BERINOVASI DAN ORIENTASI PEMBELAJARAN PENGARUNYA TERHADAP ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR SERTA DAMPAKNYA PADA KINERJA BISNIS (Studi pada Sentra Industri Kue di Kabupaten Cirebon ) - - Badawi; Wiwi Hartati (Universitas Muhammadiyah Semarang, 2011)
Purpose of this study to obtain empirical evidence and find the clarity of the phenomenon as well asconclusions about entrepreneurial orientation, market orientation and learning orientation on the ability toinnovate and its impact on business performance This thesis is expected to contribute to the development ofmanagement science, especially about the entrepreneurial orientation, market orientation and learningorientation on the ability to innovate and its impact on business performanceThe study uses descriptive and verification method that is collecting, presenting, analyzing, and testinghypotheses, and make hypotheses and make conclusions conclusions and suggestions by means of SEM analysisFrom the analysis of research data, obtained some conclusions and suggestions are: 1) entrepreneurialorientation effect on learning orientation, 2) Market orientation effect on learning orientation, 3) Theorientation of the learning effect on the ability to innovate 4) The orientation of the learning effect on the abilityto innovate, strengthen the influence of learning orientation between the entrepreneurial orientation of theability to innovate, 5)The ability to innovate to strengthen the influence of entrepreneurial orientation tobusiness performance, 6) Ability to innovate influence on business performance , 7) Market orientation did notaffect the business performance